Spiritual Support During COVID-19 in England: A Scoping Study of Online Sources - Papadopoulos, Irena (Journal of religion and health, 2021)
Spiritual support is a key element of holistic care, and better healthcare professionals training and stronger strategic guidelines become urgent in light of health disasters and emergencies, such as the COVID-19 pandemic. To this end, the aim of this study was to explore spiritual support provision within mass and social media and the websites of spiritual leaders, institutions and NHS chaplaincy units during COVID-19 in England, between March and May 2020. A scoping review design informed by Levac and colleagues’ five-staged framework was adopted, and adapted with a multi-strategy search to scope the different domains of online sources. Results revealed that spiritual support for dying patients, their families, health care staff, spiritual leaders and chaplains, had to be drastically reduced, both in quality and quantity, as well as being provided via different technological devices or domestic symbolic actions. No mention was found of a central strategy for the provision of spiritual support. This study points to the importance of developing centralized strategies to prepare healthcare systems and professionals in relation to spiritual support provision, both routinely and during health disasters and emergencies. Further research will have to explore innovative practices, in particular the role of digital technologies, in spiritual support provision.